2014
DOI: 10.1177/0829573514540266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Implementing School-Wide Positive Behavioural Interventions and Supports on Problem Behaviour and Academic Achievement in a Canadian Elementary School

Abstract: Although there is much research on School-Wide Positive Behavioural Interventions and Supports (PBIS) in the United States, there is little such research in Canada. The purpose of the current study was to provide a case study example of the relation between implementing PBIS and student academic and behavioural outcomes, as well as student perceptions of the school environment. Data were collected in one school as it moved from partial to full implementation of PBIS. The results of the study indicated positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Simonsen et al, 2012), improved perception of safety (e.g. Horner et al, 2009;Kelm, McIntosh, & Cooley, 2014), reduction in bullying behaviors (e.g. , increased attendance (e.g.…”
Section: Purposementioning
confidence: 99%
“…Simonsen et al, 2012), improved perception of safety (e.g. Horner et al, 2009;Kelm, McIntosh, & Cooley, 2014), reduction in bullying behaviors (e.g. , increased attendance (e.g.…”
Section: Purposementioning
confidence: 99%
“…1) Reduction in problem behavior: Multiple randomized controlled trials have documented reduction in problem behavior and of ice discipline referrals when PBIS Tier I practices were implemented (Bradshaw, Mitchell, & Leaf, 2010;Flannery et al, 2014;Horner et al, 2009;Kelm et al, 2014;McIntosh, Bennett, & Price, 2011;Metzler et al, 2001;Nelson et al, 2002).…”
Section: Empirical Support For Pbismentioning
confidence: 99%
“…3) Improved academic achievement: School-wide behavior support does not directly improve academic outcomes, but when students are more likely to attend school, more likely to be academically engaged in class, and more likely to ind the environment welcoming and comfortable they are also more likely to learn. At least four papers report improved academic outcomes associated with PBIS implementation Kelm et al, 2014;Lassen, Steele, & Sailor, 2006;Nelson et al, 2002). 4) Improved perception of school safety: Horner et al (2009) assessed student and staff perception of school safety and found increases when PBIS was adopted.…”
Section: Empirical Support For Pbismentioning
confidence: 99%
See 1 more Smart Citation
“…Using school-wide positive behavior support programs can curb many undesirable behaviors and identify students who need support at a more intensive level (McIntosh & Bennett, 2011;McKevitt & Braaksma, 2008;Medley, Little, & Akin-Little, 2008). However, given that more than half of all elementary school disciplinary referrals are for repeat offenders, punitive disciplinary actions have been largely unsuccessful in changing undesirable behaviors (Smith, Bicard, Bicard, & Casey, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%